Evolution and shapes of dunes - Herrmann, Hans J (Comptes rendus. Physique, 2002)
The motion of dunes and their morphology is a fascinating, largely unexplored subject. Already the barchan, the simplest moving dune, poses many questions. I will present some results of field-measurements on desert and coastal dunes. Then I will present a model which consists of three coupled equations of motion for the topography, the shear stress of the wind and the sand flux. These evolution equations are verified on the experimental data and new possibilities of simulations of dunes are put in perspective. To cite this article: H.J. Herrmann, C. R. Physique 3 (2002) 197–206. Les mouvements des dunes et leur morphologie est un sujet fascinant et peu exploré. Déjà la barchane, la dune mobile la plus simple, pose des nombreuses questions. Je présente quelques résultats des mesures sur les terrains pour des dunes côtières et désertiques. Ensuite je présenterai un modèle consistant de trois équations de mouvement couplées, une pour la topographie, une pour la force de cisaillement du vent et la troisième pour l'écoulement de sable à la surface. Ces équations sont validées auprès des données expérimentales et des perspectives nouvelles pour la simulation des dunes sont présentées. Pour citer cet article : H.J. Herrmann, C. R. Physique 3 (2002) 197–206.